Development of a physical simulation method of steel welds for fatigue crack propagation studies, on heat affected zones (2016)
In order to study the fatigue crack propagation in the Highly Affected Zone (HAZ) of structural steel weld joints, test specimens of 90 mm x 49.5 mm x 7 mm in size were used to carry out the simulations, for which a special procedure was required to be developed in the Gleeble system. By doing so, the fine grain zone, the coarse grain zone and the multi-pass zone of a weld joint were successfully reproduced separately, on different samples of the corresponding base metal, produced by FCAW. The simulated zones were reproducible, homogeneous, defect-free, residual-stress-free and large enough, besides their microstructural characteristics (such as grain size and phase percentage) were very close to their real counterparts, which made it possible to study the actual effect of HAZ microstructure on the fatigue crack propagation rate in these zones for the first time. Therefore, the development enabled to significantly applications and the advantages increase, that this technique may have, while allowing to improve the understanding of fatigue behavior in steel weld joints.